2009
DOI: 10.1128/cvi.00023-09
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Responses toLeishmania majorVirulence Factors in Healed Cutaneous Leishmaniasis and Mediterranean Visceral Leishmaniasis Patients

Abstract: Cellular and humoral immune responses of healed cutaneous leishmaniasis and Mediterranean visceral leishmaniasis patients were evaluated against results for Leishmania major virulence proteins L. major protein disulfide isomerase (LmPDI) and mitogen-activated protein kinase kinase (MAPKK). Only MAPKK induces significant peripheral blood mononuclear cell proliferation with gamma interferon production as well as antibody responses. Thus, MAPKK may be of interest in Leishmania vaccination and serodiagnosis.The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Similarly, to these results, we have recently demonstrated that LaPSA-38S, a L. amazonensis promastigote surface antigen, induced high specific IFN-γ levels in individuals immune to L. major and L. infantum infection [24]. Our previous data and those of other authors have shown Leishmania protein-specific IFN-γ levels, in immune individuals [2527]. We further showed in this study, a significant increase in the percentage of rLmlRAB and rLmlRABC-specific IFN-γ-producing CD4+ as well as CD8+ T cells, in CL recovered individuals.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, to these results, we have recently demonstrated that LaPSA-38S, a L. amazonensis promastigote surface antigen, induced high specific IFN-γ levels in individuals immune to L. major and L. infantum infection [24]. Our previous data and those of other authors have shown Leishmania protein-specific IFN-γ levels, in immune individuals [2527]. We further showed in this study, a significant increase in the percentage of rLmlRAB and rLmlRABC-specific IFN-γ-producing CD4+ as well as CD8+ T cells, in CL recovered individuals.…”
Section: Discussionsupporting
confidence: 79%
“…In the study authors theorized that these results may be useful for leishmaniasis vaccination and serodiagnosis. [ 10 ]…”
Section: Leishmaniasis Surveillance and Controlmentioning
confidence: 99%
“…In response to viral [ 20 , 21 , 22 ], parasitic [ 23 , 24 , 25 , 26 ], or bacterial [ 27 , 28 ] infections, CD4 + T cells predominantly differentiate into Th1 cells that produce inflammatory cytokines (i.e., IFN-γ and TNF-ɑ) and participate in cell-mediated immune responses, such as enhancement of the differentiation of naïve CD8 + T cells into cytotoxic T cells (CTL) for the clearance of infections of viral [ 20 , 21 , 29 ], bacterial [ 30 , 31 , 32 ], and parasitic [ 33 , 34 ] origins. CD4 + T cells can also mediate B cell differentiation and antibody production against extracellular [ 35 , 36 , 37 ] and intracellular [ 38 , 39 ] pathogens.…”
Section: Introductionmentioning
confidence: 99%